BIOLOGY AND HABITS OF Zulia colombiana (LALLEMAND) (HOMOPTERA: CERCOPIDAE) A PEST OF Brachiaria spp. GRASS - ARANGO-S., GUILLERMO; CALDERÓN-C., MARIO (Revista Colombiana de Entomología, 1981)
During 1978 heavy attacks of the spittlebug Zulia colombiana (Lallemand) in several genera of graminae in the Department of Cauca, Colombia was observed. The life cycle of the insect was studied under laboratory and greenhouse conditions. Results showed that eggs were cream with the following characteristics: size 1 mm, (0,97 to 1,17) (mean) length, by 0,30 (0,26 to 0,33) wide, incu¬bation period 18 days (12 to 24 mean) under laboratory conditions (T: 25°C, RH: 70°/o) and 15 days (12 to 18) under greenhouse conditions (T: 28°C, RH: 80%). The nymph stage showed five instars and took a total of 45 days as a mean. First instar 5 to 7 days, second 5 to 8; third 8 to 12 days; fourth instar 8 to 12 days and the fifth instar 10 to 16 days. The nymphs fed on roots and soft parts of the plant. The mate is brown in color, 10 mm length, and 4,8 mm wide. The female is dark, almost black, and is 11 mm long and 5 mm wide. Both, the head and the pronotum are metallic green. The wings show irregular spots and the last third is orange. The adult fed on the aerial part of the plant (foliage). Several natural enemies that could be utilized as biological controls were found: the fungus Metarhizium sp, a fly possibly Salpingogaster sp, and a nematode not yet identified.